2015
DOI: 10.1155/2015/843717
|View full text |Cite
|
Sign up to set email alerts
|

Engaging with Families Is a Challenge: Beliefs among Healthcare Professionals in Forensic Psychiatric Care

Abstract: Being healthcare professionals in the complex field of forensic psychiatry care (FPC) seems particularly challenging. Historically, families have almost been invisible in FPC. The aim of this study was to uncover beliefs among healthcare professionals concerning families of patients admitted for FPC. Using a hermeneutical approach inspired by Gadamer's philosophy, group interviews with healthcare professionals in four Swedish forensic psychiatric clinics were analyzed. Analysis resulted in seven key beliefs. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Furthermore, teams are often under pressure, and this can lead to a parallel process where chronically stressed services act out a repetitive cycle of re-enactment in a harmful interactive dynamic with traumatised service users (Bloom, 2011). Hörberg et al (2015) suggested that professionals sometimes regard the relatives of forensic patients as broken or difficult to trust, which can impede opportunities for family work, but our experience was that teams often made referrals for FI in exasperation hoping that the families could be “fixed” by the family work or at the least taken away for a while. Our observation was that when the professional/family system had become stuck in a trauma-organised pattern of relating, the family work allowed the opportunity for different types of conversation and relating to begin, not only within the family but also between family members and professionals.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, teams are often under pressure, and this can lead to a parallel process where chronically stressed services act out a repetitive cycle of re-enactment in a harmful interactive dynamic with traumatised service users (Bloom, 2011). Hörberg et al (2015) suggested that professionals sometimes regard the relatives of forensic patients as broken or difficult to trust, which can impede opportunities for family work, but our experience was that teams often made referrals for FI in exasperation hoping that the families could be “fixed” by the family work or at the least taken away for a while. Our observation was that when the professional/family system had become stuck in a trauma-organised pattern of relating, the family work allowed the opportunity for different types of conversation and relating to begin, not only within the family but also between family members and professionals.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, family members and friends of patients in secure settings reported they felt more informed of their loved one's mental health and treatment, further reducing the "them and us" schema (McCann, 1993). Horberg, Benzein, Erlingsson, and Syren (2015) highlighted from a health care professional's perspective the importance of family as a resource for patient recovery. Specifically, according to health care professionals, the experience of family belongingness is crucial in the patient's recovery, as the family can provide the patient with moral support and motivation (Horberg et al, 2015).…”
Section: Family Therapy In Incarcerated Settingsmentioning
confidence: 99%
“…Horberg, Benzein, Erlingsson, and Syren (2015) highlighted from a health care professional's perspective the importance of family as a resource for patient recovery. Specifically, according to health care professionals, the experience of family belongingness is crucial in the patient's recovery, as the family can provide the patient with moral support and motivation (Horberg et al, 2015).…”
Section: Family Therapy In Incarcerated Settingsmentioning
confidence: 99%
“…Families of PLWSUFC face a double peril. Hörberg et al (2015) explained that they have a mental illness and a criminal act to contend with often without preceding awareness. This brings distress to any family given the chronic nature of schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…This has resulted to myths and misconstructions being framed about this mental condition rendering the schizophrenia patients mysterious to their family members and the public eye. Where people living with schizophrenia engaged in violent acts, Hörberg, et al (2015) submitted that important legal and health consequences followed. The persons end up being referred for treatment under the forensic Psychiatric care instead of being taken to prison.…”
Section: Introductionmentioning
confidence: 99%